Interventional cardiac MRI using an add‐on parallel transmit MR system: In vivo experience in sheep. Issue 6 (19th July 2021) - Godinez, Felipe; Tomi‐Tricot, Raphael; Delcey, Marylène; Williams, Steven E.; Mooiweer, Ronald; Quesson, Bruno; Razavi, Reza; Hajnal, Joseph V.; Malik, Shaihan J.
Abstract : Purpose: We present in vivo testing of a parallel transmit system intended for interventional MR‐guided cardiac procedures. Methods: The parallel transmit system was connected in‐line with a conventional 1.5 Tesla MRI system to transmit and receive on an 8‐coil array. The system used a current sensor for real‐time feedback to achieve real‐time current control by determining coupling and null modes. Experiments were conducted on 4 Charmoise sheep weighing 33.9‐45.0 kg with nitinol guidewires placed under X‐ray fluoroscopy in the atrium or ventricle of the heart via the femoral vein. Heating tests were done in vivo and post‐mortem with a high RF power imaging sequence using the coupling mode. Anatomical imaging was done using a combination of null modes optimized to produce a useable B1 field in the heart. Results: Anatomical imaging produced cine images of the heart comparable in quality to imaging with the quad mode (all channels with the same amplitude and phase). Maximum observed temperature increases occurred when insulation was stripped from the wire tip. These were 4.1℃ and 0.4℃ for the coupling mode and null modes, respectively for the in vivo case; increasing to 6.0℃ and 1.3℃, respectively for the ex vivo case, because cooling from blood flow is removed. Heating < 0.1℃ was observed when insulation was not stripped from guidewire tips. In all tests, the parallel transmit system managed to reduce the temperature at the guidewire tip. Conclusion: We have demonstrated the first in vivo usage of an auxiliary parallel transmit system employing active feedback‐based current control for interventional MRI with a conventional MRI scanner.